Comparison of Anodic TiO2-Nanotube Membranes used for Frontside-Illuminated Dye-Sensitized Solar Cells - Mohammadpour, Fatemeh; Moradi, Mahmood; Cha, Gi; So, Seulgi; Lee, Kiyoung; Altomare, Marco; Schmuki, Patrik (ChemElectroChem, 2015)
In the present work we compare TiO2-nanotube lift-off strategies for the construction of frontside-illuminated dye-sensitized solar cells (DSSCs). Anodic nanotube layers were detached from the metallic back contact by using different techniques and transferred onto a fluorine-doped tin oxide substrate. We show that if we use an optimized potential step treatment to fabricate membranes, DSSC efficiencies can be significantly increased ( extgreekh>8 %). The improved efficiency is ascribed to higher specific dye loading and enhanced electron-transport properties of optimally fabricated TiO2-nanotube membranes.
EAM Import::2019-03-13

Conical-shaped titania nanotubes for optimized light management in DSSCs reach back-side illumination efficiencies > 8% - So, Seulgi; Kriesch, Arian; Peschel, Ulf; Schmuki, Patrik (Journal of Materials Chemistry A, 2015)
In the present work, we introduce the anodic growth of conical shaped TiO2 nanotube arrays. These titania nanocones provide a scaffold for dye-sensitized solar cell (DSSC) structures with significantly improved photon management, providing an optimized absorption profile compared with conventional cylindrical nanotube arrays. Finite difference time domain (FDTD) modelling demonstrates a drastically changed power-absorption characteristic over the tube length. When used in a back-side illumination DSSC configuration, nanocone structures can reach over 60% higher solar cell conversion efficiency ( extgreekh) than conventional tubes. The resulting extgreekh ≈ 8% represents one of the highest reported values for Grätzel type DSSCs used under back-side illumination.
EAM Import::2019-03-13

Dye-sensitized TiO2 nanotube membranes act as a visible-light switchable diffusion gate - Hwang, Imgon; Riboni, Francesca; Gongadze, Ekaterina; Iglič, Aleš; Yoo, Jeong Eun; So, Seulgi; Mazare, Anca Valentina; Schmuki, Patrik (Nanoscale Advances, 2019)
Here we report that both-end open anodic TiO2 nanotube membranes, after sensitization with a Ru(ii)-based dye, exhibit visible-light switching properties for flow-through the nanotube channels. Under illumination, the gate is in an open state providing ∼four-times faster permeation of small molecules through the membrane compared to a dark state. Switching is reversible with no apparent dye degradation being observed. Gating is possible not only of permeating dye molecules but also of nanoprobes such as polystyrene nanospheres. Supported by quantitative modelling, we attribute the switching mechanism to light-induced changes of the charge distribution at the dye/TiO2 interface which in turn alters the hydrodynamics within the anodic tube membranes. This demonstrates that these simple dye-sensitized nanotube membranes can be used as an optically addressable flow-through gate in nanofluidics.
CRIS-Team Scopus Importer:2019-12-17

Enhanced performance of dye-sensitized solar cells based on TiO2 nanotube membranes using an optimized annealing profile - Mohammadpour, F.; Moradi, M.; Lee, Kiyoung; Cha, Gi; So, Seulgi; Kahnt, Axel; Guldi, Dirk Michael; Altomare, Marco; Schmuki, Patrik (Chemical Communications, 2015)
We use free-standing TiO2 nanotube membranes that are transferred onto FTO slides in front-side illuminated dye-sensitized solar cells (DSSCs). We investigate the key parameters for solar cell arrangement of self-ordered anodic TiO2 nanotube layers on the FTO substrate, namely the influence of the annealing procedure on the DSSC light conversion efficiency. The results show that using an optimal temperature annealing profile can significantly enhance the DSSC efficiency (in our case extgreekh = 9.8%), as it leads to a markedly lower density of trapping states in the tube oxide, and thus to strongly improved electron transport properties.
EAM Import::2019-03-14

Hierarchical DSSC structures based on 'single walled' TiO2 nanotube arrays reach a back-side illumination solar light conversion efficiency of 8% - So, Seulgi; Hwang, Imgon; Schmuki, Patrik (Energy and Environmental Science, 2015)
In the present work we introduce a path to the controlled construction of DSSCs based on hierarchically structured single walled, self-organized TiO2 layers. In a first step we describe a simple approach to selectively remove the inner detrimental shell of anodic TiO2 nanotubes (NTs). This then allows controlled well-defined layer-by-layer decoration of these TiO2-NT walls with TiO2 nanoparticles (in contrast to conventional TiO2 nanotubes). We show that such defined multiple layered decoration can be optimized to build dye sensitized solar cells that (under back-side illumination conditions) can yield solar light conversion efficiencies to the extent of 8%. The beneficial effects observed can be ascribed to a combination of three factors: (1) improved electronic properties of the ``single walled'' tubes themselves, (2) a further improvement of the electronic properties by the defined TiCl4 treatment, and (3) a higher specific dye loading that becomes possible for the layer-by-layer decorated single walled tubes.
EAM Import::2019-03-13

High-Aspect-Ratio Dye-Sensitized Solar Cells Based on Robust, Fast-Growing TiO2 Nanotubes - So, Seulgi; Lee, Kiyoung; Schmuki, Patrik (Chemistry - A European Journal, 2013)
The mechanical attachment of TiO2 nanotube layers to a substrate can be a determining factor for the performance of these layers in dye-sensitized solar cells (DSSCs). Self-organized TiO2 nanotube layers grown in an electrolyte that contained lactic acid are shown to have considerably improved anchoring on the Ti metal substrate, which allows the construction of stable and efficient solar cells with >50 extgreekmm nanotube length.
EAM Import::2019-03-13

Inducing a Nanotwinned Grain Structure within the TiO2 Nanotubes Provides Enhanced Electron Transport and DSSC Efficiencies >10% - So, Seulgi; Hwang, Imgon; Yoo, Jeong Eun; Mohajernia, Shiva; Mackovic, Mirza; Spiecker, Erdmann; Cha, Gi; Mazare, Anca Valentina; Schmuki, Patrik (Advanced Energy Materials, 2018)
Titania is one of the key materials used in 1D, 2D, and 3D nanostructures as electron transport media in energy conversion devices. In the present study, it is shown that the electronic properties of TiO2 nanotubes can be drastically improved by inducing a nanotwinned grain structure in the nanotube wall. This structure can be exclusively induced for “single-walled” nanotubes with a high-temperature treatment in pure oxygen atmospheres. Nanotubes with a twinned grain structure within the tube wall show a strongly enhanced conductivity and photogenerated charge transport compared to classic nano-tubes. This remarkable improvement is exempliﬁed in the electronic properties by using nanotwinned TiO2 nanotubes in dye-sensitized solar cells where a signiﬁcant increase in efﬁciency of up to 10.2% is achieved. <p
Keywords: nanotwinned; TiO2 nanotubes; conductivity; DSSCs

NH3 treatment of TiO2 nanotubes: from N-doping to semimetallic conductivity - Al-Thabaiti, Shaeel A.; Hahn, Robert; Liu, Ning; Kirchgeorg, Robin; So, Seulgi; Schmuki, Patrik; Basahel, Sulaiman N.; Bawaked, Salem M. (Chemical Communications, 2014)
In the present work we show that a suitable high temperature ammonia treatment allows for the conversion of single-walled TiO2 nanotube arrays not only to a N-doped photoactive anatase material (which is already well established), but even further into fully functional titanium nitride (TiN) tubular structures that exhibit semimetallic conductivity.
EAM Import::2019-03-12

Open top anodic Ta3N5 nanotubes for higher solar water splitting efficiency - Grigorescu, Sabina Georgiana; So, Seulgi; Yoo, Jeong Eun; Mazare, Anca Valentina; Hahn, Robert; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work we grow self-organized Ta2O5 nanotube layers in a H2SO4/NH4F electrolyte at various elevated temperatures. Under optimized conditions we obtain 4 extgreekmm long nanotubes that are well adherent to the substrate and can be grown very homogenous over large surface areas. Moreover, the key advantage of this approach is that an open top morphology (initiation layer free) is obtained. After a suitable conversion treatment in NH3 atmosphere Ta3N5 nanotubes are obtained, that after (Co-Pi+Co(OH)x) modification provide, under AM 1.5G illumination conditions, a photoelectrochemical current response of 4.7 mA cm-2 at +1.23 V vs RHE.
EAM Import::2019-03-08

Ru-doped TiO2 nanotubes: Improved performance in dye-sensitized solar cells - So, Seulgi; Lee, Kiyoung; Schmuki, Patrik (Physica Status Solidi-Rapid Research Letters, 2012)
In the present work we use a series of Ti–Ru alloys, with minor amounts of Ru (0.01, 0.02, 0.05 and 0.2 at%) to grow anodic self-organized Ru-doped TiO2 nanotube layers. When used in dye-sensitized solar cells (DSSCs), the nanotube layers with an optimum amount of Ru (0.02 at% Ru in the alloy) show a considerable increase in solar cell efficiency ( extgreekh = 5.2%) under AM1.5 (100 mW/cm2) conditions compared with non-doped TiO2 nanotubes ( extgreekh = 4.3%).
EAM Import::2019-03-13

Single-Walled TiO2 Nanotubes: Enhanced Carrier-Transport Properties by TiCl4 Treatment - Hwang, Imgon; So, Seulgi; Mokhtar, Mohamed; Alshehri, Abdelmohsen; Al-Thabaiti, Shaeel A.; Mazare, Anca Valentina; Schmuki, Patrik (Chemistry - A European Journal, 2015)
In the present work we report significant enhancement of the photoelectrochemical properties of self- organized TiO2 nanotubes by a combined -coringof classic nanotubes followed by an appropiate TiCl4 treatment. We show that, except for the expected particle decoration, a key effect of the TiCl4 treatment is that the electron transport characteristics in TiO2 nanotubes can be drastically improved, for example, we observe an enhancement of up to 70 % in electron-transport times.
EAM Import::2019-03-13

Ultrafast Growth of Highly Ordered Anodic TiO 2 Nanotubes in Lactic Acid Electrolytes - So, Seulgi; Lee, Kiyoung; Schmuki, Patrik (Journal of the American Chemical Society, 2012)
In the present work, we show that fully functional self-organized TiO2 nanotube layers can be electrochemically grown with an unprecedented growth rate if lactic acid (LA) is used as an additive during anodization. The main effect of LA addition is that it allows performing nanotube growth at significantly higher anodization voltage than in the LA free case, and this without dielectric oxide breakdown (``burning''). As a result, for example, 15 extgreekmm tube thick nanotube layers, suitable for a use in dye-sensitized solar cells (DSSCs) can be grown in 45 s and 7 extgreekmm tubes suitable for water splitting can be grown in 25 s.
EAM Import::2019-03-13